2006
DOI: 10.1007/s10815-006-9030-8
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus DNA exposure and embryo survival is stage-specific

Abstract: Purpose: Human papillomavirus (HPV) has been shown to disrupt late-stage implanting embryos. The objectives were (a) to assess the development of early embryos exposed to HPV DNA and (b) to analyze the blastocyst hatching process after HPV exposure. Methods:The study involved exposing two-cell and 4-8-cell mouse embryos to DNA fragments from either HPV type 16, type 18 or DQA1 (control). The embryos were incubated for 120 h and assessed. Results: HPV 16 and 18 inhibited two-cell embryo development. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 33 publications
(29 reference statements)
2
48
1
2
Order By: Relevance
“…Interestingly, the presence of the virus has been associated with increased wastage and miscarriage rates in both animals and humans, through transformation of cells, gene interruption and loss of chromosome heterozygosity, or fragmentation of the host DNA and/or apoptosis 6,8,13,34 . Moreover, the effect on embryo development seems to be stage related, from cellular instability at the two-cell level, through a decrease in blastocyst formation and up to the inhibition of the blastocyst hatching process 9,31 . Similarly, the secondary outcome parameters set for this review appear not to be affected by the presence of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the presence of the virus has been associated with increased wastage and miscarriage rates in both animals and humans, through transformation of cells, gene interruption and loss of chromosome heterozygosity, or fragmentation of the host DNA and/or apoptosis 6,8,13,34 . Moreover, the effect on embryo development seems to be stage related, from cellular instability at the two-cell level, through a decrease in blastocyst formation and up to the inhibition of the blastocyst hatching process 9,31 . Similarly, the secondary outcome parameters set for this review appear not to be affected by the presence of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Possible consequences of fetal exposure to HPV are not well defined, but a clinical study performed in women undergoing IVF reported a significant reduction of pregnancies in patients with papillomavirus cervical infection compared with uninfected women (21). In addition, several experimental studies have demonstrated the role of HPV in causing pregnancy loss by transmission of viral genes to oocytes and determining DNA fragmentation and apoptosis of embryonic cells (19,22,23). Little evidence is present regarding the possibility that sperm infected with HPV is able to interfere with the embryo development when injected in the oocyte cytoplasm (such as during the ICSI procedure).…”
Section: Discussionmentioning
confidence: 99%
“…In men HPV sperm infections can be long-lasting (24 months) and are frequently associated with anti-sperm antibodies that may further reduce male fertility [5]. The presence of HPV virions that can bind two distinct sites along the equator of the spermatozoa's heads [5,6,7,8] may not only have a detrimental effect on sperm parameters [6,8,9] but also on gamete interaction, since in vitro experiments have demonstrated that spermatozoa can not only transfer HPV virions [10] to the oocyte, but the transferred HPV virions also induce stage-specific maturation arrest in infected embryos [11]. In untreated women with transient HPV infections, the median number of months between the first negative HPV measurement and the viral load maximum and the last HPV-negative measurement, irrespective of the HPV type, was 15.7 months and 11.9 months, respectively [4].…”
Section: Introductionmentioning
confidence: 99%